Firegirl - Abbott, Tony 1952- (New York Scholastic Inc., 2010)
A middle school boy's life is changed when Jessica, a girl disfigured by burns, starts attending his Catholic school while receiving treatment at a local hospital.
Keywords: Coming of age -- Fiction; Catholic schools -- Fiction; Schools -- Fiction; Burns and scalds -- Fiction; Disfigured persons -- Fiction